Historical Archaeology in the East Midlands and East Africa: Personal Reflections. (1st November 2013) - Posnansky, Merrick
<x xml:space="preserve">Abstract</x> After obtaining his doctorate in archaeology at Nottingham University in 1956, Merrick Posnansky conducted research and taught in Ghana, Kenya, and Uganda for twenty years. He served in a succession of positions, including Curator of the Uganda Museum, Director of the African Studies Program at Makerere University College, Uganda, and Professor of Archaeology at the University of Ghana. Posnansky joined the faculty of the University of California at Los Angeles in 1977. He has conducted research in fourteen African countries and trained generations of Africanist researchers. Author of numerous publications, Posnansky prepared this article for a symposium at the 2013 annual conference of the Society for Historical Archaeology to provide a brief overview of the development of the fields of historical archaeology of British, African, and African diaspora sites over the last half century.